DETERMINATION OF INTERNAL AND EXTERNAL FACTORS CAUSE PULP TISSUE DISEASES - Hendari, Ratnawati; Siregar, Irma HY; Oktaviani, Frida (Jurnal Kesehatan Masyarakat, 2015)
Factors of the oral cavity (internal) and external factors play an important role in health status of the teeth and mouth. This study was aimed to determine the causes of internal and external diseases of the pulp tissue in the North Karangasem village of Batang regency.This case study was carried out by survey methods. The independent variables were internal factors (plaques, saliva hydration, viscosity, and pH) and external factors (behavioral, health services, and genetics). The dependent variable was pulp tissue disease (pulpitis, pulp gangrene, and gangrene radix). Plaque index was measured by PHP-M, while saliva hydration, saliva viscosity, and saliva pH were measured using GC Dental Saliva Indicator guide. External factors was assessed using a close questionnaire to 99 respondents observed by purposive randomly sampling with slovin formula.  The results showed that the pulp tissue disease was caused by internal factor was saliva pH (44%) and saliva viscosity (64%), while external factors were behavioral (64%) namely incorrect brushing time (54%), snacking habits of sticky sweet (70%), and snacking frequency more than 3 times a day (50%). This study concluded that major cause of pulp tissue disease in North Karangasem village communities of Batang regency was saliva pH and behavior. Faktor dari dalam rongga mulut (internal) maupun faktor dari luar (eksternal) memegang peranan yang penting dalam mempengaruhi status kesehatan gigi dan mulut. Tujuan penelitian ini adalah untuk mengetahui determinasi  faktor internal dan eksternal penyebab penyakit jaringan pulpa pada masyarakat di Kelurahan Karangasem Utara Kabupaten Batang. Jenis penelitian ini adalah survey diskriptif dengan metode yang digunakan adalah case study. Faktor internal yang diamati adalah plak indeks, hidrasi saliva, viskositas saliva dan pH saliva. Faktor eksternal, meliputi lingkungan, perilaku, pelayanan kesehatan, dan keturunan. Cara mengukur plak indeks menggunakan metode PHP-M . Pengukuran hidrasi saliva, viskositas saliva, dan pH saliva menggunakan panduan GC Dental Saliva Indicator.  Penilaian faktor eksternal menggunakan kuesioner. Pengambilan sampel menggunakan teknik purposive random sampling.  Jumlah sampel  sebanyak 99 responden usia 15-44 tahun.  Hasil penelitian menunjukkan bahwa penyakit jaringan pulpa yang disebabkan oleh faktor internal adalah pH saliva (44%) dan viskositas saliva (64%). Faktor eksternal adalah perilaku (64%) akibat waktu menyikat gigi yang salah (54%) dan kebiasaan ngemil dalam memilih jenis makanan manis melekat (70%) dan frekuensi ngemil > 3x sehari (50%). Kesimpulan penelitian ini adalah aktor penyebab utama penyakit jaringan pulpa pada masyarakat di Kelurahan Karangasem Utara kabupaten Batang adalah pH saliva dan perilaku masyarakat.